Key terminology in biomaterials and biocompatibility. (June 2019) - Ghasemi-Mobarakeh, Laleh; Kolahreez, Davood; Ramakrishna, Seeram; Williams, David
Abstract: Biomaterials have gained much interest as a very important category of materials because of their wide application in medicine and benefit to patient such as increased longevity and improved quality of life. The biocompatibility of biomaterials is an important issue, and many researches have been devoted during the past decades in this field. In this review, we will focus on basic concepts and key terminologies in the fields of biomaterials and biocompatibility. Moreover, the most recent definitions of the terms related to biomaterials and biocompatibility provided in the 2018 Chengdu consensus conference are stated. Some standard methods for evaluating the concepts related to biomaterials and biocompatibility are also listed in this article.